Perhitungan Gaya-Gaya yang Bekerja pada Rantai Jangkar KM. Naga Sejahtera III - Wibowo, Riyanto; Sugiantoro, Wasis (Marine Science and Technology Journal, 2022)
Indonesia is a maritime country because most of its territory is surrounded by oceans. This geographical location makes Indonesia need a reliable sea transportation model. One of the sea transportation models used is the ship. Anchor is one of the components in the ship. Ship anchors in general usually consist of chains and ballast. The role of the anchor on the ship is very vital, especially when the ship is anchored. This study aims to calculate the forces acting on the KM anchor chain. Prosperous Dragon III. The results showed that the tensile stress on the anchor chain of Naga Sejahtera III was 161.35 kg/cm2 and on the right chain 138.71 kg/cm2. The bending moment acting on the Naga Sejahtera III ship on the commonlink is 4.33 kg/cm2 , at the endlargelink and endlink is 5 kg/cm2 . The shear stress acting on the anchor chain on the left of the Naga Sejahtera III ship is 80.67 kg/cm2 and on the right chain is 69.35 kg/cm2.